Dual EMCV-IRES-integrated dengue virus can express an exogenous gene and cellular Mdm2 integration suppresses the dengue viral replication - Teramoto, Tadahisa (Frontiers in Microbiology, 2025)
Flaviviruses transmit through a wide range of vertebrate and arthropod hosts, while the other genera in Flaviviridae replicate in a limited set of vertebrate hosts. Flaviviruses possess a 5′ cap in their genome RNA for translation, while the other genera utilize their internal ribosome entry site (IRES) sequences instead of a 5′ cap. In this study, the translational modification to add an IRES sequence was examined. An IRES sequence derived from encephalomyocarditis (EMCV) was inserted into dengue virus serotype 2 (DENV2); a non-structural (NS) polyprotein was translated by IRES separately from 5′ cap-induced structural polyprotein translation. It was revealed that the IRES-integrated DENV2 is prevented from replicating in C6/36 mosquito cells, suggesting that the 5′ cap is an advantageous mechanism for flavivirus translation in invertebrate species. I further created dual IRES-integrated DENV2, in which a non-viral gene can be expressed by the flanking IRESs. The insertion of eGFP fluorescently visualized the virus spread. The renilla luciferase (Rluc) integration enabled the viral replication quantification. It was also revealed that a cellular gene, Mdm2, which antagonizes tumor suppressor protein p53 (TP53), could terminate the viral replication in BHK21 cells. Thus, the modifications of the DENV genome with IRES and the subsequent foreign gene could be utilized for controlling viral replications.